2021
DOI: 10.1002/lno.11940
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial input of herbicides has significant impacts on phytoplankton and bacterioplankton communities in coastal waters

Abstract: Herbicide use has increased very rapidly worldwide in recent decades, and some of these herbicides eventually enter the ocean. At present, herbicide pollution in the ocean has become a global environmental problem. Here, in a field investigation of 22 commonly used herbicide residues (triazine, phenylurea, and amide) in the Bohai Sea and the Yellow Sea, we found that the detection rate of herbicide residues within 100 km from shore was 100%. Notably, triazine herbicides have reached concentrations (up to 12.07… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…This is also supported by synchronous low DSi concentrations of the Yellow River water (Li et al, 2022) and low Chl a concentrations of the Bohai seawater (Cui et al, 2024). In addition, due to the long residence time of freshwater, diatom production in summer could be suppressed by the pollution of atrazine that is heavily used in spring, but this effect is only detected within limited areas (Yang et al, 2021). Figure 5.…”
Section: The Wsrs On the Yellow River Is Primary Water Mixing Control...mentioning
confidence: 99%
See 1 more Smart Citation
“…This is also supported by synchronous low DSi concentrations of the Yellow River water (Li et al, 2022) and low Chl a concentrations of the Bohai seawater (Cui et al, 2024). In addition, due to the long residence time of freshwater, diatom production in summer could be suppressed by the pollution of atrazine that is heavily used in spring, but this effect is only detected within limited areas (Yang et al, 2021). Figure 5.…”
Section: The Wsrs On the Yellow River Is Primary Water Mixing Control...mentioning
confidence: 99%
“…Diatoms and dinoflagellates are the two dominant phytoplankton in the Bohai Sea, with diatoms accounting for ∼80% of total phytoplankton abundance (Li et al., 2021; Wei et al., 2022). The Bohai Sea is one of the most populated catchments in the world and has been greatly perturbed by human activities, such as offshore oilfields, petrochemical plants, and aquaculture areas (Ding et al., 2021; Liu et al., 2017; Xin et al., 2019; Yang et al., 2021). The excessive nutrient load has resulted in eutrophication and stimulated harmful algae blooms, which are currently devastating the Bohai Sea ecosystem (Ding et al., 2021; Liu et al., 2017; Maure et al., 2021; Wang et al., 2019; Wu et al., 2013; Xin et al., 2019; Zheng et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their immense abundance and level of activity, these organisms can rapidly respond to environmental gradients and changes employing a multitude of biological interplays with other microbes and higher organisms (Bunse & Pinhassi, 2017). Phytoplankton and bacterioplankton are closely interconnected communities in marine environments through the exchange of organic matter and inorganic nutrients (Yang et al, 2021). Their microscale interactions underpin ocean biogeochemistry (Smriga et al, 2016), and their community structure is key to the functioning of ecosystems (Fuhrman, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study found that some dominant offshore species (e.g., Phaeodactylum tricornutum and Chaetoceros sp.) were extremely sensitive to triazine herbicides, and atrazine at ambient concentrations (1 μg L − 1 ) significantly inhibited their photosynthesis (approximately 57% of photosynthetic genes were significantly downregulated) and weakened their chlorophyll a fluorescence intensity 9 , 10 . Marine phytoplankton contribute approximately 50% of the total global primary productivity and play a vital role in global carbon cycling 11 .…”
Section: Introductionmentioning
confidence: 99%